UK monetary and fiscal policy since the Great Recession - An evaluation - Vo Phuong Mai Le; David Meenagh; Patrick Minford; Ziqing Wang (Cardiff University, Cardiff Business School, 2023)
This paper explores the economic impacts of the Bank of England's quantitative easing policy, implemented as a response to the global financial crisis. Using an open economy Dynamic Stochastic General Equilibrium (DSGE) model, we demonstrate that monetary policy can remain effective even when nominal interest rates have reached the zero lower bound. We estimate and test the model using the indirect inference method, and our simulations indicate that a nominal GDP targeting rule implemented through money supply could be the most effective monetary policy regime. Additionally, our analysis suggests that a robust, active fiscal policy regime with nominal GDP targeting could significantly enhance economic stabilization efforts.
Keywords: 330; Quantitative easing; Financial friction; SOE-DSGE; Indirect inference; Zero bound